Community-Based Participatory Research: Insights, Challenges, and Successes From the Perspectives of Frontline Recruiters and Investigators - Nita Vangeepuram; Kezhen Fei; Crispin Goytia; Devin Madden; Giselle Corbie-Smith; Carol R. Horowitz (Journal of Participatory Research Methods)
Employment of community-based participatory research (CBPR) strategies has helped address limitations of traditional research approaches, but we still do not have a full understanding of how study teams successfully conduct research with populations who experience health disparities. To gain insights into the unique successes and challenges of research teams conducting National Institutes of Health (NIH) funded community-engaged research studies, we conducted an online survey with 120 investigators identified through NIH RePORTER and 106 members of the academic study team (research staff) who assisted with recruitment. We examined descriptive statistics and used Chi-square analysis to compare responses between investigators and staff. Most studies targeted low-income, racial/ethnic minority populations and reported high recruitment and retention rates. The most common collaborators were community-based organizations, and the most common study purpose was to evaluate an intervention. There was generally consensus between investigators and staff about effective recruitment and retention strategies, barriers, and facilitators. However, there were also some critical differences, including perceptions about community partner roles and the value of staff input into study design and methods. After the presentation of our key findings, we share best practices for successful recruitment and retention in health disparities research using CBPR approaches.